Hukum Islam: Antara Wahyu Tuhan dan Pemikiran Manusia - Marzuki Umar; Kurniati Kurniati; Misbahuddin Misbahuddin (BUSTANUL FUQAHA: Jurnal Bidang Hukum Islam, 2022)
The purpose of this study is to find out how reason and revelation go hand in hand in the formation of Islamic law. The method used is a literature study with a qualitative approach. The results of the study show that reason and revelation are both the basis for giving birth to Islamic law. This study also analyzes that there is no contradiction between reason and revelation in principle. In fact, the position between reason and revelation can be parallel, but theologically it is revelation that is the source of inspiration for reason so that revelation (as a subject) has a higher position. On the other hand, reason cannot be a source of revelation, because reason is a creation while revelation is the word of God. The conclusion of this research is that today's Islamic law must be able to maximize its scientific reasoning (reasoning) in order to find hidden meanings in the texts of the Qur'an and hadith in answering the problems of life in the world without neglecting the benefits of the hereafter.